(NiZBRANNYE SO^INENIQ W DWUH TOMAH (B/s (N~ASTX (B2s - (NpU[KIN(B, (NaLEKSANDR sERGEEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1978)
(NwO WTOROJ TOM SO^INENIJ a(B.(Ns(B. (NpU[KINA WO[LI(B: (NROMAN W STIHAH (B"(NeWGENIJ oNEGIN(B", (NIZBRANNYE DRAMATI^ESKIE I PROZAI^ESKIE PROIZWEDENIQ(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs; (NrUSSKIE PROIZWEDENIQs